Effect of total quality management practices and knowledge management on innovation performance in private higher education institutions in Oman - Al Jabri, Ahmed Rashid Saleem (2024)
Innovation performance (INNOP) in the service sector is a new concept and the higher education system is the backbone of the economy. However, quality management at Omani private higher education institutions needs improvement to ensure better quality of education. This study investigates the relationship between total quality management (TQM) practices (top management support, student focus, continuous improvement, and employee involvement) and INNOP of Omani private higher education institutions. The mediating role of knowledge management (KM) and the moderating role of organizational learning capability (OLC) was also examined. This study collects data from 350 employees of Omani private higher education institutions using a cross-sectional survey. Partial least squares-structural equation modeling (PLS-SEM) was used to assess the hypothesized relationships. The results show that TQM practices are negatively associated with INNOP due to challenges such as the high workload of academic staff, lack of quality training opportunities, and support from top management. Besides, KM mediates the relationship between TQM practices and INNOP as it promotes competitive advantage. Moreover, OLC moderates the relationship between TQM practices and INNOP, as Omani private higher education institutions are continuously improving their educational quality and learning culture to be more innovative. This study contributes to the body of knowledge by applying the Resource-Based View (RBV) and Quality Management (QM) theories to assess the linkages of INNOP, TQM practices, KM and OLC in the context of Omani private higher education institutions. Additionally, stakeholders in the education sector and private higher education institutions could gain essential insights from the empirical research findings to improve the quality and innovation performance of education and gain a competitive advantage.